Comparison of shooting time characteristics and shooting posture between high- and low-performance archers - Lau, J. S.; Ghafar, R.; Zulkifli, E. Z.; Hashim, H. A.; Sakim, H. A. M. (Annals of Applied Sport Science, 2023)
Background. Archery is a precision sport that requires high levels of consistency and reproducibility in the shooting movement to achieve the highest score.